Time Matters Strategy: Adaptive Group Counseling to Optimize Time Management for New Students - Shanti, Dharma; Ainnurohmah, Dinda; Aini, Khurin; Pratiwi Kuswardani, Hasna' (Educational Psychology Journal, 2025)
New students often struggle to manage their time effectively due to various academic and non-academic demands. This study aims to determine new students' time management skills and test the effectiveness of the Time Matters Strategy through adaptive group counselling. The study employs a quantitative approach with a quasi-experimental one-group pre-test post-test design. The sample consisted of 5 new students selected through purposive sampling. The instruments used were a time management questionnaire and a self-evaluation questionnaire. Data analysis was performed using a paired sample t-test. The results showed a significant improvement in the time management skills of new students after participating in three sessions of Time Matters Strategy group counselling, with the average pre-test score of 74.80 increasing to 88.80 on the post-test (p = 0.004; Cohen's d = -2.720). In addition, participants reported positive changes in their thoughts, emotions, and behaviour, including reduced anxiety, increased motivation, and becoming accustomed to using effective time management methods. Group counselling with the Time Matters Strategy effectively improves the time management skills of new students, so it can be used as an alternative psychological intervention in higher education settings.